Utility of bone marrow examination (BME) in the diagnosis of pyrexia of unknown origin (PUO) - Padmaja, Kanne; Hashmiya, Syeda Saba; Sudhaharan, Sukanya; Teja, Vijay Dharma; Patil, Madhusudhan; Uppin, Shantveer; Subbalaxmi, Malladi Venkata Surya (The Journal of Infection in Developing Countries, 2023)
Introduction: Bone marrow examination (BME) is a useful tool in the diagnosis of haematological and non-haematological diseases. It plays an important role in early diagnosis of the underlying cause of pyrexia of unknown origin (PUO) and can influence the management of patients. Bone marrow aspiration (BMA) plays a very important role in establishing a definitive diagnosis in cases of PUO. The aim of this study was to review the indications and usefulness of bone marrow aspirates sent for microbiological evaluation as a diagnostic tool with histopathological correlation. Methodology: A prospective study was conducted from 1 January 2017 to 30 September 2019 in the Department of Microbiology and Pathology on the bone marrow aspirates of patients of all groups. Results: A total of 148 bone marrow aspirates were included. The cases were categorized as classical PUO (n = 81/148, 54.7%), nosocomial PUO (n = 4 /148, 2.7%), neutropenic PUO (n = 18/148, 12.1%), and immunocompromised PUO (n = 45/148, 30.4%), among which were systemic lupus erythematosus cases n = 8/45 (22.2%), human immunodeficiency virus positive cases n = 10/45 (17.7%), and renal transplant cases n = 27/45 (60%). A total of 28 BMAs were positive for microorganisms, out of which bacterial pathogens were n = 12 (42.8%), mycobacterial n = 12, 42.8%, fungal (n = 3, 10.7 %), and viruses (n = 1, 3.5%). Conclusions: This study helped in highlighting the role of bone marrow examination as an important diagnostic method in the diagnosis of infectious diseases.